Transference and Pedagogical Eros in the Educational Relationship: Affections in Educational Practices between Pedagogy and Psychoanalysis - Vincenzo Salerno; Leonardo Rigoni (Formazione & Insegnamento, 2022)
Since some time, many authors stated that our Culture has removed emotional and transference dynamics from the educational relationship. For this reason, Pedagogy has to think about pedagogical eros and pedagogical transference as dynamics which always are active in the relationship between educators and students. Therefore, this operation requires a group-training of skills related to the way of thinking and the way in which personal and Community educational actions are thought. Psychoanalysis could give to Pedagogy epistemological and practical insights which are interesting in order to use pedagogical eros and transference. The article aims to understand how pedagogical transference could be used in the educational actions and, on the other hand, it attempts to reflect on what characteristics should have a vocational training aware to pedagogical eros.